Penyuluhan Anti Perundungan dan Etika Berkomunikasi pada Siswa-siswi SD Al-Ittihadiyah Laut Dendang - Laily Ramadhani; Irwan Nopian Sinaga; Trans Ningsih (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
The purpose of carrying out this community service activity is to increase students' knowledge and understanding related to bullying behavior and communication ethics. This community service activity is carried out by providing counseling in the form of information dissemination for students at school. Through this activity, it is hoped that teachers can convey information related to how to minimize bullying that occurs in schools against students. The participants in this community service activity totaled 25 students from SD Al-Ittihadiyah. The results of this community service showed the active participation of students, where as many as 10 students asked questions related to bullying material and 3 teachers asked questions about what is the role of teachers or schools in helping students to reduce bullying that occurs in schools. From the questions asked, there was active interaction between the resource person and the participants interspersed with games and games to warm up the atmosphere. Apart from that, the students and the counseling participants became aware of what bullying is, both verbal and non-verbal bullying, and how to communicate ethically.